An Overview of the Diversity of Aquatic Insects in Assam, North-East India - Danswrang Basumatary (Emerging Issues in Environment, Geography and Earth Science Vol. 7, 2024)
India is one of the world’s mega-biodiversity hotspot nations. The country is one of the world’s 17 Mega biodiverse countries, accounting for 7-8% of all documented species. A class of arthropods known as aquatic insects can be found on or on the surface of lacustrine or riverine ecosystems where they complete their life cycle in water bodies. Eight main insect orders live their whole lives in the freshwater habitat. Aquatic insects are a taxonomically varied, ecologically significant, and fascinating collection of creatures found in Lentic freshwater systems. They are recognised to play an important role in nutrient processing and cycling since they are classified as shredders, filter feeders, deposit collectors, and predators. The functioning of aquatic ecosystems is greatly influenced by aquatic insects. The current study aims to examine the relative abundance of insects in various microhabitats of the study site Assam and the North Eastern States of India. A significant diversity of aquatic insects, which is indicative of the strength and abundance of the aquatic ecosystem, may be found in the northeastern section of India and various parts of Assam. In most of the research sites, it was discovered from the entire study that insects from the orders Odonata, Hemiptera, and Coleoptera were most prevalent, followed by those from the orders Diptera and Ephemeroptera. The order Coleoptera accounted for 59% of all known aquatic insect species. The studied locations are discovered to have the least number of insects from the Orders Plecoptera, Trichoptera, Hymenoptera, and Collembola. In Northeast India and several parts of Assam, there were no records of aquatic insects from the Orders Neuroptera/Megaloptera and Lepidoptera.